Antioxidants and Cognitive-Behavioral Therapy in Patients with Functional Dyspepsia - T. V. Sapozhnikova; S. A. Parfenov; T. E. Yesina; K. V. Sapozhnikov; A. N. Smirnov; A. A. Paulov; D. M. Rizakhanov; O. A. Rizakhanova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Аim: development of an algorithm for the use of antioxidant cognitive-behavioral therapy in adult patients with functional dyspepsia.Material and methods. The study included 112 adult patients with functional dyspepsia receiving the antioxidant drug Cytoflavin containing succinic acid, inosine, nicotinamide and riboflavin, and cognitive behavioral therapy according to the method of Beck and Jacobson in addition to the main therapy (prokinetics, proton pump inhibitors, psychotropic drugs).Results. Of the total group, 74 patients had an optimal response to the inclusion of an antioxidant and psychotherapy in the treatment regimen (increased quality of life and reduced anxiety) and 38 patients had the insignificant response. It has been established that the main predictors of the successful use of an extended treatment regimen are the patient's disadaptation in relation to the disease, a recent stress factor, the duration of functional dyspepsia, the presence of an overlap syndrome (combination with other functional gastrointestinal disorders).Conclusions. Based on the collection of a small amount of anamnestic information (the duration of functional dyspepsia, the presence of an acute stress factor in the anamnesis), the assessment of the presence of an overlap syndrome and disadaptation in relation to the patient to his illness, the value of the discriminant function is calculated. After comparing it with a threshold, the probability of a positive response to a combination of antioxidant and cognitive-behavioral therapy is estimated. The developed prediction algorithm is valid (sensitivity — 91 %, specificity — 73 %, accuracy — 84.8 %) and allows to optimize the definition of treatment tactics for a patient with functional dyspepsia.